AMOC Variability and Watermass Transformations in the AWI Climate Model. (8th October 2021) - Sidorenko, D.; Danilov, S.; Streffing, J.; Fofonova, V.; Goessling, H. F.; Scholz, P.; Wang, Q.; Androsov, A.; Cabos, W.; Juricke, S.; Koldunov, N.; Rackow, T.; et al.
Abstract: Using the depth ( z ) and density ( ϱ ) frameworks, we analyze local contributions to AMOC variability in a 900‐year simulation with the AWI climate model. Both frameworks reveal a consistent interdecadal variability; however, the correlation between their maxima deteriorates on year‐to‐year scales. We demonstrate the utility of analyzing the spatial patterns of sinking and diapycnal transformations through depth levels and isopycnals. The success of this analysis relies on the spatial binning of these maps which is especially crucial for the maps of vertical velocities which appear to be too noisy in the main regions of upwelling and downwelling because of stepwise bottom topography. Furthermore, we show that the AMOC responds to fast (annual or faster) fluctuations in atmospheric forcing associated with the NAO. This response is more obvious in the ϱ than in the z framework. In contrast, the link between AMOC and deep water production south of Greenland is found for slower fluctuations and is consistent between the frameworks. Plain Language Summary: The variability and trends in Atlantic meridional overturning circulation (AMOC) are some of the most important characteristics of an ocean model simulation that are relevant for climate. Usually, the AMOC is computed as a meridional transport (from bottom to top) of zonally integrated flow along constant depth levels ( z ‐AMOC). However, water in the ocean generally flows along the density surfaces. In low latitudes, they are nearly flat and the general picture given by z ‐AMOC is highly relevant. In high latitudes, where the most important processes of dense water formation and sinking take place, density surfaces are sloping, and the z ‐AMOC gives a distorted image of the real circulation. This is why recent studies underlined the importance of computing the AMOC as a function of density in addition to AMOC as the function of vertical coordinate. In this paper, we analyze the fundamental differences with respect to AMOC variability in both frameworks in a 900‐year run with the AWI climate model. We demonstrate that the latitudinal position of overturning maxima, amplitude, and variability show substantial differences between the frameworks. We suggest that the ϱ ‐AMOC and watermass transformation framework should be used routinely in standard analyses, including forthcoming intercomparison projects. Key Points: Patterns of sinking and diapycnal transformation across depth levels and isopycnals, respectively, can be used to study AMOC variability The AMOC subpolar maximum is largely driven by internal transformations The density framework illustrates the interplay between surface buoyancy flux and interior‐mixing